2012
DOI: 10.1007/s40145-012-0019-8
|View full text |Cite
|
Sign up to set email alerts
|

Ceramics for high level radioactive waste solidification

Abstract: Several countries reprocess their nuclear spent fuel using the Purex process to recover U and Pu as MOX fuel. The high level radioactive waste (HLW) produced during this reprocessing is a complex mixture containing both radioactive (fission products, minor actinides) and non-radioactive elements. Since HLW shows high rate heat release and contains some long half-life and biologically toxic radionuclide, its treatment and disposal technology is complex, difficult and high cost. HLW treatment and disposal become… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 106 publications
(42 citation statements)
references
References 21 publications
1
40
0
1
Order By: Relevance
“…Leaching experiments exhibit quite good resistance of Ln' 1-x Ln" x PO 4 matrices in a strongly acid HNO 3 solution (pH 1-2) at room temperature (Figure 8 & 9). The results of leaching experiments for Ln' 1-x Ln" x PO 4 are close to [20] for GdPO 4 in strongly HCl and HNO 3 solutions (pH 1-2) corresponding to value of ~10 -2 g L -1…”
Section: Synthesis and Thermal Behavior Of Nanopowders In Lapo 4 -Yposupporting
confidence: 64%
See 3 more Smart Citations
“…Leaching experiments exhibit quite good resistance of Ln' 1-x Ln" x PO 4 matrices in a strongly acid HNO 3 solution (pH 1-2) at room temperature (Figure 8 & 9). The results of leaching experiments for Ln' 1-x Ln" x PO 4 are close to [20] for GdPO 4 in strongly HCl and HNO 3 solutions (pH 1-2) corresponding to value of ~10 -2 g L -1…”
Section: Synthesis and Thermal Behavior Of Nanopowders In Lapo 4 -Yposupporting
confidence: 64%
“…In many previous works, the monazite-type lanthanum orthophosphate (LaPO 4 ), and xenotime one (YPO 4 ) has been suggested as matrices for radioactive waste immobilization (radioactive rare earth elements or trivalent actinides) and sensors [1][2][3][4][5][6][7][8]. Nanopowder-based ceramics designed for immobilizing purpose should possess high chemical resistance and isomorphic capacity, high durability and thermal stability.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, radionuclides are easy to escape from glass forms. In recent years, many results showed that ceramic forms exhibit superior long-term stability, radiation tolerance and leaching resistance to glass forms, and most actinides and fission products can be incorporated into polycrystalline phases [3][4][5]. Perovskite phases, particularly SrTiO 3 , are good host phases for the immobilization of actinides and some long-lived fission products [6,7].…”
Section: Introductionmentioning
confidence: 99%